2011
DOI: 10.1007/s00586-011-1848-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of idiopathic hypertrophic thoracic pachymeningitis

Abstract: Idiopathic hypertrophic spinal pachymeningitis (IHSP) is a comparatively rare disease characterized by hypertrophic inflammation of the dura mater and clinical symptoms that progress from local pain to myelopathy. We report a case of IHSP followed up for 20 years in a 46-year-old man. Expansive laminoplasty was performed in 1991, and this case has been previously reported by a co-author. After 17 years, the patient's gait disturbance returned. Physical examination and imaging confirmed IHSP that had developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Early disease recurrence was reported in 8 cases (Table 2). Tsutsui et al 33 reported 5 cases of recurrence, with a follow-up of more than 10 years, stating that the course of the disease follows one of 3 patterns: 1) sustained remission, 2) relapse with corticosteroid resistance, or 3) relapse with corticosteroid dependence. Tosa et al 32 reported that a higher recurrence and poorer prognosis was seen in patients with active inflammatory signs at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Early disease recurrence was reported in 8 cases (Table 2). Tsutsui et al 33 reported 5 cases of recurrence, with a follow-up of more than 10 years, stating that the course of the disease follows one of 3 patterns: 1) sustained remission, 2) relapse with corticosteroid resistance, or 3) relapse with corticosteroid dependence. Tosa et al 32 reported that a higher recurrence and poorer prognosis was seen in patients with active inflammatory signs at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports of IHSP have been limited to short-term follow-up after the initial treatment. According to previous reports, with long term follow-up exceeding 5 years, recurrence was noted in three of five cases 28) . In this regard, repeated follow ups are desirable in patient with IHSP even after successful treatment.…”
Section: Discussionmentioning
confidence: 57%
“…However, the mean follow-up period of reviewed patients was short (1.3 years; range, 1 week-4 years). Recently, Tsutsui et al20) has reported a long-term follow-up of 5 years of IHSP with a high recurrence rate and a review of the literature. Disease progression has been reported to be related to increased cerebro-spinal fluid protein and cells16).…”
Section: Discussionmentioning
confidence: 99%